Agricultural food industries Reality and development prospects by benefiting from the Malaysian experience: التجربة الماليزية - جقموق, كفاح (Latakia University Journal - Economic and Legal Sciences Series, 2025)
The experience of Southeast Asian countries has attracted global attention, as these nations transitioned from being among the poorest in the world to being classified as industrial countries. Despite the crisis they faced since mid-1996, these countries achieved high growth rates, managed to attract investments, and increased their exports, creating job opportunities and boosting their GDP. Among these countries is Malaysia, which focused on education, openness to the global market, and the use of advanced technology. While it adopted a policy of import substitution and provided necessary protection for its national industries, the success of these industries was contingent upon meeting certain economic standards. Given the importance of industry and its role in economic growth, this research examines the reality of agro-food industries, the challenges they face, and potential solutions for their development to enhance their contribution to the GDP. Additionally, the study explores Malaysia’s reliance on industrial development as a cornerstone of its economic progress and investigates the feasibility of utilizing this experience to advance agro-food industries and achieve food security. This research addresses the agro-food industries in Syria, shedding light on the current situation, challenges, and future opportunities. It emphasizes the significance of this sector in achieving food security and fostering economic development while analyzing the difficulties associated with weak infrastructure, low product quality, and limited competitiveness. Furthermore, it reviews Malaysia’s successful experience in industrialization and export, highlighting its pioneering strategies such as attracting foreign investments, improving infrastructure, and promoting industries with comparative advantages. Employing a descriptive-analytical methodology, the study aims to offer practical solutions to stimulate Syria’s agro-food industries, proposing plans to enhance production efficiency, utilize local resources, and diversify exports to achieve sustainable competitiveness.